2015
DOI: 10.1007/s12576-015-0376-5
|View full text |Cite
|
Sign up to set email alerts
|

KATP channels and MPTP are involved in the cardioprotection bestowed by chronic intermittent hypobaric hypoxia in the developing rat

Abstract: The aim of this study was to explore the mechanism underlying the cardioprotection bestowed by chronic intermittent hypobaric hypoxia (CIHH) against ischemia/reperfusion (I/R) injury in developing rats. Neonatal male rats were subjected to CIHH treatments that simulated an altitude of 3000 m a.s.l. for 28 days (CIHH28) and 42 days (CIHH42), respectively, or no treatment (control). The left ventricular function of isolated hearts was evaluated. The ultra-microstructure, superoxide dismutase (SOD) activity and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…In contrast, the selective sarcK ATP channel blocker HMR 1098 did not alter CCNH-induced tolerance to ischemia and reperfusion. This result is consistent with published data indicating the participation of mitoK ATP channel in the infarct-limiting effect of ischemic preconditioning (Yellon and Downey 2003) and adaptation to intermittent hypoxia (Kolar et al 2005;Bu et al 2015) Our studies and those of other investigators have documented that mitoK ATP channel is involved in the signaling pathway of cardioprotective effect of exogenous opioids (McPherson and Yao 2001;Peart et al 2008;Maslov et al 2009;Gross et al 2012). This result is consistent with published data on participation of opioid receptors in the infarct reducing effect of CCNH (Maslov et al 2013) and chronic intermittent hypoxia (Estrada et al 2016).…”
Section: Disscussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, the selective sarcK ATP channel blocker HMR 1098 did not alter CCNH-induced tolerance to ischemia and reperfusion. This result is consistent with published data indicating the participation of mitoK ATP channel in the infarct-limiting effect of ischemic preconditioning (Yellon and Downey 2003) and adaptation to intermittent hypoxia (Kolar et al 2005;Bu et al 2015) Our studies and those of other investigators have documented that mitoK ATP channel is involved in the signaling pathway of cardioprotective effect of exogenous opioids (McPherson and Yao 2001;Peart et al 2008;Maslov et al 2009;Gross et al 2012). This result is consistent with published data on participation of opioid receptors in the infarct reducing effect of CCNH (Maslov et al 2013) and chronic intermittent hypoxia (Estrada et al 2016).…”
Section: Disscussionsupporting
confidence: 93%
“…The results of our experiments with atractyloside were somewhat unexpected since we had previously demonstrated that adaptation to chronic continuous hypoxia blocks the opening of MPT pore in response to ischemia/reperfusion of the isolated rat heart (Maslov et al 2015). It has been shown that atractyloside abolished infarct reducing effect chronic intermittent hypoxia (Bu et al 2015). Prior studies have shown that MPT pore plays an important role in the pathogenesis of apoptotic cell death (Halestrap 2010).…”
Section: Disscussionmentioning
confidence: 63%
“…Oxygen radicals produced during I/R are important factors for myocardial injury Bu et al 2015). In this study, the cardioprotective effects of Nari was canceled by non-specific K ATP blocker Gli and specific mitoK ATP blocker 5-HD, which suggests Nari protects heart against I/R injury through opening of K ATP , especially mitoK ATP .…”
Section: Discussionmentioning
confidence: 53%
“…Recently, one study showed that Nari exerts anti-ischemic effects on rat heart which is likely to be mediated by the activation of mitochondrial BK channels (Testai et al 2013). And another study reported that Nari attenuated pressure overload-induced cardiac hypertrophy (Zhang et al 2015). However,the mechanism of Nari protection on heart against I/R injury is far from clear.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic intermittent hypobaric hypoxia (CIHH), which is similar to ischemic preconditioning and high altitude hypoxia adaptation, confers cardiac protection against ischemia/reperfusion (I/R) injury in rats [6][7][8][9]. Enhancement of resistance against calcium overload is one of the striking mechanisms of CIHH.…”
Section: Introductionmentioning
confidence: 99%